Oxybleptes davisi (Notman, 1924) in Minnesota (Coleoptera, Staphylinidae, Staphylininae, Xantholinini) - Smetana, Aleš (Zootaxa, 2013)
The occurrence of numerous male specimens of Oxybleptes davisi (Notman, 1924) near Duluth in northern Minnesota is reported, including the special collecting circumstances. This is the first record of Oxybleptes davisi in Minnesota, which extends the distributional range of the species considerably toward the west.